Zero echo time MRI-only treatment planning for radiation therapy of brain tumors after resection. (October 2017) - Boydev, C.; Demol, B.; Pasquier, D.; Saint-Jalmes, H.; Delpon, G.; Reynaert, N.
Highlights: Synthetic CT numbers are generated from a new ZTE MRI dataset for the head. We use an atlas propagation scheme in combination with our new correction method. The case of bone resection surgery prior to radiotherapy is studied. More accurate results are produced than with the conventional T1-w MRI dataset. Abstract: Using magnetic resonance imaging (MRI) as the sole imaging modality for patient modeling in radiation therapy (RT) is a challenging task due to the need to derive electron density information from MRI and construct a so-called pseudo-computed tomography (pCT) image. We have previously published a new method to derive pCT images from head T1-weighted (T1-w) MR images using a single-atlas propagation scheme followed by a post hoc correction of the mapped CT numbers using local intensity information. The purpose of this study was to investigate the performance of our method with head zero echo time (ZTE) MR images. To evaluate results, the mean absolute error in bins of 20 HU was calculated with respect to the true planning CT scan of the patient. We demonstrated that applying our method using ZTE MR images instead of T1-w improved the correctness of the pCT in case of bone resection surgery prior to RT (that is, an example of large anatomical difference between the atlas and the patient).